2020
DOI: 10.21203/rs.3.rs-15541/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quality of Life among Infertile Couples in Gaza City, Palestine

Abstract: Background: Infertility is an important health problem affecting the quality of life accompanied by significant emotional and psychological consequences. Infertile couples living with emotional disturbances face challenges with less success of infertility treatment. Purposes: This study aimed to investigate the quality of life of infertile couples who seek In-Vitro Fertilizations (IVFs) by gender in Gaza city, Palestinian. Methods and materials: A cross sectional study was conducted, from Feb 2018 to Nov 2018,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…In the present systematic review data has been collected from various past studies conducted on the quality of life. The four studies [1,4,7,9] which have been included compared the quality of life of Infertile Women with Fertile women and Six studies [2,3,5,6,8,10] compared the quality of life of infertile women with infertile men as an infertile couples. As well these studies utilizes the WHOQOL, Ferti QOL and SF 36 questionnaire to assess the quality of life ; along with this other domains like general health of Infertile women (GHQOL 28), Linda berg Questionnaire for sexual Satisfaction, Social Support Scaling, Beck's inventory for depression were also used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present systematic review data has been collected from various past studies conducted on the quality of life. The four studies [1,4,7,9] which have been included compared the quality of life of Infertile Women with Fertile women and Six studies [2,3,5,6,8,10] compared the quality of life of infertile women with infertile men as an infertile couples. As well these studies utilizes the WHOQOL, Ferti QOL and SF 36 questionnaire to assess the quality of life ; along with this other domains like general health of Infertile women (GHQOL 28), Linda berg Questionnaire for sexual Satisfaction, Social Support Scaling, Beck's inventory for depression were also used.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies [2,3,5,6,8,10] showed that in general in infertile couples which compared the quality of life of infertile women with infertile men revealed that the mean males' scores of FertiQoL and its subscales (emotion, mind/body, social, core, tolerability and treatment) were significantly higher than females' scores (p<0.05). The mean total of FertiQoL increased with better education, however, decreased with increase of age, duration of marriage, duration of infertility and number of IVF attempts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation